2018
DOI: 10.1186/s12886-018-0912-1
|View full text |Cite
|
Sign up to set email alerts
|

Programme choice for perimetry in neurological conditions (PoPiN): a systematic review of perimetry options and patterns of visual field loss

Abstract: BackgroundVisual field loss occurs frequently in neurological conditions and perimetry is commonly requested for patients with suspected or known conditions. There are currently no guidelines for how visual fields in neurological conditions should be assessed. There is a wide range of visual field programs available and the wrong choice of program can potentially fail to detect visual field loss. We report the results of a systematic review of the existing evidence base for the patterns of visual field loss in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…The Goldmann perimeter was reported as the second most commonly used perimeter for manual kinetic perimetry. This systematic review also found that the patterns of visual field defects varied greatly across the four conditions (Hepworth & Rowe 2018). The 24-2 program has been found to be used extensively in neurological conditions (Hepworth & Rowe 2018).…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…The Goldmann perimeter was reported as the second most commonly used perimeter for manual kinetic perimetry. This systematic review also found that the patterns of visual field defects varied greatly across the four conditions (Hepworth & Rowe 2018). The 24-2 program has been found to be used extensively in neurological conditions (Hepworth & Rowe 2018).…”
Section: Introductionmentioning
confidence: 82%
“…The FF-120 program selected in the other conditions was replaced by the monocular Esterman program for stroke; the reason being the distribution of stimuli locations are clustered closely in the nasal visual field but more sparsely located in the temporal visual field in the FF-120. A systematic review reported both the static 30-2 program and manual kinetic perimetry were commonly used in studies across all four conditions (Hepworth & Rowe 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations